Analisis Implementasi Undang-Undang Nomor 16 Tahun 2019 tentang Perkawinan terhadap Tingkat Penurunan Perkawinan Usia Dini - Karningsih Karningsih; Maliki Aji Prakoso; Ruri Fintayana (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the relationship between the implementation of Law Number 16 of 2019 on Marriage and socioeconomic status with public awareness of early marriage in Wirosari District, Grobogan Regency. The phenomenon of early marriage in this area remains high despite the existence of regulations that set a minimum marriage age. A quantitative approach was used, with data collected through questionnaires, interviews, and documentation. The research population consisted of 169 couples who married early in the last three years, with a sample of 43 couples selected through purposive sampling. The data were analyzed using the product moment correlation test to determine the relationships between the variables. The results show that the implementation of Law Number 16 of 2019 has no significant relationship with public awareness of early marriage, indicating that despite the existence of the regulation, the public's understanding of the importance of the minimum marriage age is still not optimal. Conversely, socioeconomic status has a positive and significant relationship with public awareness, indicating that the higher the socioeconomic status, the higher the public's awareness of the negative impacts of early marriage.